The Sudden Stratospheric Warming Events in the Antarctic in 2024 - Yucheng Zi; Zhenxia Long; Jinyu Sheng; Gaopeng Lu; Will Perrie; Ziniu Xiao (Geophysical Research Letters, 2025)
Abstract In July and August 2024, two consecutive stratospheric sudden warming (SSW) events (termed SW07 and SW08) occurred over Antarctic, both featuring a rapid 17°C temperature rise at 10 hPa and significant stratospheric polar vortex (SPV) deceleration. SW07 occurred at the earliest winter time of the year recorded in the satellite era (1979 to present). The study found that, strong blocking highs affected stratospheric warming via nonlinear planetary wave prior to SW07, and the substantial sea ice loss over Antarctic Ross Sea and Amundsen Sea likely created favorable conditions for the formation of these blocking highs. Furthermore, the stratospheric preconditioning significantly amplified the intensity of the planetary waves. A downward‐propagating negative Southern Annular Mode (SAM) signal after SW07 supported blocking highs, creating a favorable circulation for planetary wave perturbations prior to SW08. In addition, enhanced ozone transport from low latitudes to the pole during SW07 and SW08 contributed to ozone recovery.